2018
DOI: 10.1186/s12884-018-1943-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition during pregnancy and early development (NuPED) in urban South Africa: a study protocol for a prospective cohort

Abstract: BackgroundAdequate nutrition during pregnancy is important to ensure optimal birth outcomes, maternal health and offspring development. However, little is known about the dietary intake and nutritional status of pregnant women residing in urban South Africa. Therefore, the Nutrition during Pregnancy and Early Development (NuPED) cohort study was initiated to assess early nutrition-related exposures predictive of early childhood development in urban South Africa.MethodsThe aims of this prospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 74 publications
2
53
0
1
Order By: Relevance
“…Epidemiological studies have shown that the prenatal period of development largely determines the occurrence of lifestyle and civilization diseases in later life [1,2,3,4]. Proper preparation of a woman for pregnancy has a significant impact on embryo genesis.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that the prenatal period of development largely determines the occurrence of lifestyle and civilization diseases in later life [1,2,3,4]. Proper preparation of a woman for pregnancy has a significant impact on embryo genesis.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional status of pregnant women is a main priority that must be fulfilled by the family in order to mothers are able to deliver healthy babies (Symington et al, 2018) (Wu et al, 2004). Many factors affect the nutritional status of pregnant women including their low education.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational weight gain measurements can be determined by weight, height, and gestational age (Committee, O. N. S. D. P., & Institute, O. M., 1990). Measurement of weight (kg) and height (cm) is determined based on the nearest 0.05 kg for weight, and 0.1 cm for height (Symington, 2018). Detailed description of the standard operating procedure (SOP) for weight and height measurement are provide in appendices.…”
Section: Maternal Eating Behaviourmentioning
confidence: 99%
“…Pregnancy outcomes measurement will be take in the end of pregnancy. The infant is weighted on a calibrated scale with minimum of clothing, namely only a vest, and without nappy, and recorded to the nearest 5 g (Symington, 2018). The categories neonatal birth weight measured according to Chan, et al (2011) are divide into three groups: very low birthweight (<1.500g), low birthweight (<2.500g), and normal birthweight (2.500 or more).…”
Section: Completion/final Evaluation Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation